Efecto de sustratos orgánicos en el crecimiento de plantulas de Iryanthera tessmanii Mgt. en vivero Puerto Almendra, Loreto - Perú 2019 - Rodriguez Flores, Victor Aldo (2021)
The experiment was conducted in the nursery of CIEFOR Puerto Almendra FCF - UNAP, San Juan Bautista, Maynas, Loreto. Objective: to determine the increase in height and diameter; survival and quality of natural regeneration seedlings of Iryanthera tessmannii Mgt. in nursery with different substrates. The area was 10 m2 divided into 15 plots of 2.0 m x 0.3 m each; a simple randomized experimental design, control, 4 treatments and 3 replications were used. Witness t0 = 100% natural soil; treatments: t1 = 50% natural soil + 50% decomposed sawdust. t2 = 45% natural soil + 45% decomposed sawdust + 5% chicken manure + 5% sand. t3 = 80% decomposed sawdust + 10% chicken manure + 10% sand, t4 = 60% natural soil + 20% decomposed sawdust + 15% chicken manure + 5% sand. The results indicate that the control t0 presented the best increase in height with 5.07 cm and the greatest increase in diameter was in treatment t3 with 0.50 mm; 100% survival was recorded in the control (t0) and treatments t2 and t3; the quality of the seedlings in general was good.